TANGGUNGJAWAB PIDANA TERHADAP PELAKU TINDAK PIDANA PENIPUAN DAN PENGGELAPAN (PUT. NO. 1103/PID.B/2021/PN.JKT.SEL): Criminal Responsibility Against the Persons of the Criminal Acts of Fraud and Embracement (Decision. NO. 1103/PID.B/2021/PN.JKT.SEL) - Pratama, Alvinza Aditya; Prastopo (AMICUS CURIAE, 2024)
one of the causes of criminal acts of fraud is that the perpetrator can convince the victim with his deceit and false prestige. the defendant deceived the victim by pretending to be a State Civil Apparatus (ASN) and used the victim to commit his crime by committing fraud and embezzlement. This is in line with the beginning of the case which is the object of this research. The research method used in writing this thesis is a normative legal research method. This research is analytical descriptive in nature, using secondary legal data and primary, secondary and tertiary legal materials, collected from the results of library research, then processed qualitatively. The results of data processing from research results are concluded with the deductive method. Based on the research that has been done, it can be concluded that the criminal responsibility applied by the Panel of Judges is not quite right, the perpetrators should have applied criminal responsibility using two articles, namely the crime of fraud and embezzlement. The Panel of Judges when examining and deciding cases is more careful based on the facts of the trial, the evidence is available so that there is no mistake in deciding a criminal case.